The Effect Of Various Saturated Hydraulic Conductivity Of the Pitcher To Water Content In Sandy Loam Soil - Bertha Ollin Paga' (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Pitcher Irrigation is one of the artificial water supply techniques to overcome the lack of soil water content. The Pitcher Irrigation can save water so it is suitable for use on dry land. The research purposes was to determine the effect of various hydraulic conductivity of the picther on changes in soil water content around the pichter through program simulation. The methods used are direct measurement methods in the field and simulation methods. The measurement and simulation results are then calibrated with a solver and validated to obtain a small RMSE value and R2 was high. The results showed that the hydraulic conductivity of the picther had a significant effect on the soil water content. If the higher the hydraulic conductivity of the picther, the higher the water content around this pcther. And if the hydraulic conductivity of the picther is lower, the water content around the picther be lower. From the results of model validation, it can be said that the simulation program in this study is feasible to use because the value obtained R2 is 56.1%.